IMPLEMENTASI NEO VISIBILITAS HILAL MABIMS DI INDONESIA (IAIN Tulungagung, 2022)
ABSTRACT This paper focuses on discussing how theimplementation of Neo Visibility Hilal MABIMS inIndonesia when it is in a system that applies in acountry that also has its own method of determiningthe beginning of the month of Qamariyah. Thisresearch data is sourced from data on how theimplementation of Neo Visibility Hilal MABIMS inIndonesia is also enriched with several previousresearch results related to this reality. The resultsshow that since 1972, the Ministry of Religious Affairshas established the Hisab Rukyat Agency (BHR), whichis in charge of conducting hisab and rukyatul hilal todetermine the beginning of the month of Qamariyah,especially for religious days. The beginning of themonth is marked by the appearance of the hilal abovethe horizon, but this limit on the height of the hilalgives birth to differences of opinion. The Indonesiangovernment sets the standards and criteria for settingthe beginning of the month with imkanur rukyat. TheImkanur rukyat is the minimum limit of visible hilal.This is because the position of the hilal variesdepending on the matlak Keywords: MABIMS, Neo Visibility Hilal, ImkanurRukyat, Beginning of the Month ofQomariyah